The correlations of resilience of the geriatric population in Botswana: A cross sectional study - Mhaka-Mutepfa, Magen (Magyar Gerontológia, 2022)
According to Botswana’s Current statistics for 2021, people aged 60 and above would make up 8.9% of the population. As people age, they face a plethora of challenges; mental, legal, social, health, economic, environmental, and political, in addition to ageism and marginalization. Therefore, they need resilience to deal with these challenges that emanate from the aging process, the development of care needs, and the depletion of resources. However, in Africa, there is anecdotal evidence that some older people cannot cope with their lives, let alone carer responsibilities caused by HIV related death and other risk factors. For older people to flourish, they need resilience to achieve, endure, develop and sustain their health and well-being in the face of adversity. The degree of success and impact on their resilience is undocumented. The research will therefore determine the correlates with resilience and establish ways to curb the risk factors.